Islamisation of Laws in Pakistan? - Rashida Patel (Karachi Faiza Publishers, 1986)
An exposition of the recent process ostensibly for the Islamisation of laws, questioning whether the new laws and proposed legislation is truly Islamic, and their effects on the conditions of life in Pakistan.
Include Glossary, Index and Abbreviations.
Rashida Patel has paricipated at a number of conferences and written articles on the current process of Islamisaion in Pakistan.
Keywords: Pakistan -- Islamic law -- Islamic law, Pakistan